2023
DOI: 10.3390/app13042277
|View full text |Cite
|
Sign up to set email alerts
|

Modal Identification of Train Passenger Seats Based on Dynamic Tests and Output-Only Techniques

Abstract: Railways are one of the most efficient and widely used mass transportation systems for mid-range distances, also being pointed out as the best strategy to reach European Union decarbonisation goals. However, to increase railways attractiveness, it is necessary to improve the quality of the ride, namely its comfort, by decreasing the vibration at the passenger level. This article describes the experimental vibration modal identification of train seats based on a dedicated set of dynamic tests performed on Alfa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This study evidences the importance of carbody natural frequencies on seat transmissibility [25]. Following the same approach as Ribeiro et al [53], Silva et al [55] expanded the experimental setup on 1st and 2nd class seats of Alfa Pendular trains to investigate its transmissibility and modal identification in real-world conditions. Authors found that seat movements depend on foam's inability to absorb vibration and the carbodyʹs natural frequencies.…”
Section: Transmissibilitysupporting
confidence: 57%
See 3 more Smart Citations
“…This study evidences the importance of carbody natural frequencies on seat transmissibility [25]. Following the same approach as Ribeiro et al [53], Silva et al [55] expanded the experimental setup on 1st and 2nd class seats of Alfa Pendular trains to investigate its transmissibility and modal identification in real-world conditions. Authors found that seat movements depend on foam's inability to absorb vibration and the carbodyʹs natural frequencies.…”
Section: Transmissibilitysupporting
confidence: 57%
“…Therefore, the influence of the seat structural frame and foam leather cover on transmissibility was proved. This was the first experiment that contemplated all aspects of seat dynamics on seat transmissibility, namely the effect of the seat cushionʹs flexibility and carbody components on seat transmissibility [55]. Figure 4 presents the simplified experimental setup used by Ribeiro et al [53] and the expanded experimental setup developed by Silva et al [55].…”
Section: Transmissibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, the standard determines acceleration measurements at interface surfaces where vibrations are transmitted to the user. However, it is well known that the seat modifies vibration transmission [50][51][52][53]. Additionally, the floor represents the closer location between the users and the carbody.…”
Section: Whole-body Vibration Evaluationmentioning
confidence: 99%